2017
DOI: 10.13189/mst.2017.040102
|View full text |Cite
|
Sign up to set email alerts
|

Promising Effect of Processing Parameters on Yarn Properties in Rotor Spinning

Abstract: Fabric characteristics significantly depend on the physical properties of yarn and the qualities of rotor yarn greatly governed by processing parameters. The aim of this study is to observe the effect of processing parameters such as rotor diameter and speed on the physical properties of yarn in rotor spinning process. Mixing of spinning waste with the virgin cotton is a common phenomenon in rotor spinning. 0.11 sliver hank of 100% cotton fibre with 65% virgin cotton and 35% wastage was used to produce 12 Ne y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…is is because twill handloom weaves are denser, while plain handloom fabrics are porous. e same conclusion was given by Rajib Al Mamun [25].…”
Section: Effect Of Pillingsupporting
confidence: 77%
“…is is because twill handloom weaves are denser, while plain handloom fabrics are porous. e same conclusion was given by Rajib Al Mamun [25].…”
Section: Effect Of Pillingsupporting
confidence: 77%
“…For these reasons CV m % and IPI values of yarns are lower at lower main vacuum pressure. Hairiness is also comparatively lower at 6.0kPa because increased turbulence boosts the disengagement which consequences in adverse yarn hairiness properties [4]. The decrease in the number of fibers with leading and trailing hooks contributes to the improvement of yarn tenacity mainly [19].…”
Section: Resultsmentioning
confidence: 99%
“…Rotor spinning is the best process for utilizing the cotton waste that was obtained from carding, comber and ring spinning due to lower production cost, ample reduction in space and workforces and flexibility to automation. Now, it has been getting a stronger position in the field of spun yarn manufacture day by day [4][5][6][7][8]. Several investigations have clarified the matter that machine parameters affect the yarn properties ominously [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results of several investigations have revealed that machine parameters significantly affect the physical and mechanical properties of yarn [15][16][17]. Rotor yarns are less irregular compared to the ring-spun yarn because of multiple doubling [18]. Douglas [19] noted that high-speed modem machinery has resulted in overall quality improvement of rotor yarn.…”
Section: Introductionmentioning
confidence: 99%